TALAK MELALUI SHORT MESSAGE SERVICE - Dede Anwar Musadad; Hasan Bisri; Ayi Ishak Sholih Muchtar (Istinbath | Jurnal Penelitian Hukum Islam, 2019)
This research is supported by the very rapid development of science and information technology at this time bringing a new paradigm in understanding the various problems that arise among Muslims. One type that may be affected by technological advances itself is the problem of divorce lafadz via Short Message Service (SMS). Where the issue of divorce via SMS is prevalent in several Islamic countries such as Malaysia, Saudi Arabia, including Indonesia and many other Islamic countries that have begun to raise the discourse about divorce via SMS. Of course the events of this new discourse have reaped many pro and contra polemics among the ulama. The method used in this research is library research method. The determination is in accordance with the characteristics of the problem under study. The determination of the use of this method is based on the opinion of Winarno Surakmad (1992: 139) which states that this method is intended for deepening and deeper study aimed at solving problems that exist in the present. Then this research method uses qualitative research methods, namely: analyzing data from specific data to be drawn to a general conclusion. After doing the research, the conclusion is: Talaki law via SMS is valid, it is applied to divorce by writing. The implication is that both are messages of divorce through non-verbal (spoken) text. The reason for the fall of divorce by sending an SMS is because writing (kitabah) is one way of providing an understanding of the intended purpose of the person writing it, which is why in this case writing is punished the same as direct speech if it is done simultaneously with the intention.